The implementation of a novelty concept and measurement model for a developing B2B marketplace - ILIESCU, R I (2019)
Regardless of the market on which the company operates - B2B or B2C, brand and customer experience are the keys to success in the modern world. The B2C companies succeeded in adapting to the new trends, while B2B companies didn’t keep pace and missed the opportunity to experience the competitive advantage. The purpose of this work is to assess the brand equity through its elements – brand associations, brand attitudes, brand loyalty and other services and to identify the metrics such as Customer Lifetime Value and Retention that enforce the overall customer equity (Fig. 3.2.1). The literature was analysed and the approaches regarding brand equity and customer equity and the linkage between them were reviewed. Subsequently, the model proposed by Leone et al (2006) guided research in order to answer to the following questions: “Does a brand differentiate a distributor?” and “Are the brand equity and customer equity related in the Romanian developing B2B market?”, The quantitative research applied in this paper on a sample of 110 people from the cash- generators category showed that the brand equity is influenced by loyalty in a proportion of 29.9%. However, the conclusion is that it cannot be assumed a linear relation between brand and customer equity in the current research, from the perspective of a tyre and construction materials distributor, that operates in a developing economy. The recommendations highlights loyalty as an essential asset for Dynamic 92 who experiences long-term relationships and promising recommendations (see Net promoter score is over 70%) However, the customers are not alike and therefore the implementation of Customer Lifetime Value as a managerial KPI used in modern economies, assists the sales managers to evaluate the purchasing behaviour of up mentioned customers, to monitor their retention and the customer’s cost centre. This project could generate the company’s empowerment by the novelty and differentiation in the Romanian environment and it ensures the conditions for the company to compete with international distributors, on equal terms/positions.